Nasopharyngeal Carcinoma Ex Pleomorphic Adenoma: Case Report and Comprehensive Literature Review - Tokarz, Ellen L.; Ong, Adian A.; Burke, Mark S. (Case Reports in Otolaryngology, 2021)
Carcinoma ex pleomorphic adenoma (CXPA) is an epithelial malignancy that transforms from benign pleomorphic adenomas (PA) at a rate of 1.5% after 5 years and 10% after 15 years. The average age of reported nasopharyngeal CXPA is 56.7 years. However, the present case describes a 19-year-old making this case exceptionally rare. Standard treatment is wide local excision with adjuvant treatment. We report the demographics, presentation, treatment, and outcomes of 8 cases of nasopharyngeal CXPA. While surgical excision is the mainstay of treatment, negative margins can be difficult to obtain at the skull base, and we report a recurrence rate of 50% in nasopharyngeal primaries. Due to the aggressive nature of the disease and high rate of recurrence, the majority of patients in our review received adjuvant radiation with some receiving adjuvant chemotherapy in addition.